SISWA, GURU, DAN MORALITAS PADA LONTAR SILAKRAMANING AGURON-GURON - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Aguron-guron is a learning process given by a teacher to his students. The aguron-guron education system is a process of learning about moral education, with the hope that it will achieve the development of noble mental attitude and character by practicing the teachings of God as applied in various religious literature. religion is contained in a lontar manuscript, containing advice about obligations, manners, student and teacher relations, and the courtesy of a student in following the learning process. Based on the background of the aforementioned background, an important issue that will be discussed in this paper is: how is the relationship between teacher and student? and how the moral teachings contained in the aguron-guron edu- cation according to the Sila Kramaning Aguron-Guron ejection? Lontar Silakramaning Aguron-Guron is a didactic text that contains important teachings namely: The relationship of teachers and students in the education process is that teachers must be able to set an example to students, besides teachers must also be able to teach science; also the moral instilled in the teachings of Lontar Silakramaning Aguron-Guron is a moral which has the essence of nobility and good behavior.